Chemical composition of the Kaempferia galanga L. essential oil and its in vitro and in vivo antioxidant activities - Wang, Si-Yu; Cai, Lei; Yang, Na; Xu, Fang-Fang; Wu, Yun-Shan; Liu, Bo (Frontiers in Nutrition, 2023)
Introduction Oxidative stress is closely related to the development of many diseases. Essential oils (EOs) show potent antioxidant activity from natural sources. Kaempferia galanga L. is an important medicine rich in high-value essential oil (KGEO). However, the antioxidant activity of KGEO remains to be fully studied. Methods Chemical composition of KGEO was analyzed using gas chromatography-mass spectrometry (GC-MS). The antioxidant activity was determined using the DPPH, ABTS, hydroxyl radical scavenging assays and reducing power assay in vitro. A zebrafish model was used to evaluate the protective effect of KGEO against H2O2-induced oxidative stress damage in vivo. Results The major components of KGEO were found to be trans ethyl p-methoxycinnamate (32.01%), n-pentadecane (29.14%) and trans ethyl cinnamate (19.50%). In vitro pharmacological results showed that KGEO had good free radical scavenging capacity in DPPH, ABTS, and hydroxyl radical scavenging assays (IC50 values: 19.77 ± 1.28, 1.41 ± 0.01, and 3.09 ± 0.34 mg/mL, respectively) and weak reducing capacity in the reducing power assay (EC50 value: 389.38 ± 4.07 mg/mL). In vivo zebrafish experiments results indicated that the survival rate and heart rate increased, and ROS generation, cell death, and lipid peroxidation were attenuated after KGEO treatment. In addition, a decrease in malondialdehyde (MDA) levels and increases in superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) activities were observed in the KGEO-treated groups. Discussion This study validated the in vitro and in vivo antioxidant activities of KGEO, which provides a theoretical basis for a profound study of KGEO and its application in the pharmaceutical, food and cosmetic industries.